Mean Platelet Volume as a Surrogate Marker for Platelet Activation in Patients With Idiopathic Pulmonary Fibrosis. (May 2016) - Ntolios, P.; Papanas, N.; Nena, E.; Boglou, P.; Koulelidis, A.; Tzouvelekis, A.; Xanthoudaki, M.; Tsigalou, C.; Froudarakis, M. E.; Bouros, D.; Mikhailidis, D. P.; Steiropoulos, P.
Background: Idiopathic pulmonary fibrosis (IPF) is associated with a prothrombotic state. Aim: To study mean platelet volume (MPV) and Platelet Distribution Width (PDW) as markers of platelet activation and their potential association with lung function in patients with recently diagnosed IPF. Materials and Methods: This study included 56 patients with IPF (age 64.9±7.4 years) and 79 controls (age 64.2 ± 5.9 years). Results: An inverse relation was demonstrated between platelet count and MPV in the control group but not among patients with IPF. Platelet count was significantly lower in patients with IPF compared with controls (230 ± 60 vs 256 ± 75 × 10 3 /μL, P = .038). Conversely, MPV was higher in patients versus controls (10.3 ± 1.2 vs 9.8 ± 1.2 fl, P = .024), while there was no difference between the groups in PDW. Respiratory function was, as expected, significantly impaired in patients with IPF versus controls in terms of forced expiratory volume in first second (FEV1 ; 67.2 ± 23.1 vs 102.6 ± 15.9% of predicted value, P < .001), forced vital capacity (FVC; 65.3 ± 21 vs 95.2 ± 16.1% of predicted value, P < .001), FEV1 /FVC (83.1 ± 15 vs 87.5 ± 6.4%, P = .041) and partial pressure of oxygen in arterial blood (PaO2 ; 67.1 ± 10.3 vs 81.5 ± 15.2 mm Hg, P < .001). No significant correlation was seen between MPV and FVC ( r = −.1497, P = .275), MPV and lung diffusion capacity for carbon monoxide ( r = .035, P = .798) and total lung capacity ( r = .032, P = .820). Conclusions: Patients with IPF exhibit higher MPV values and lower platelet count. Further studies are needed to assess the clinical implications of these findings.